2001
DOI: 10.1002/1521-3773(20010302)40:5<930::aid-anie930>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Regiodivergent and Catalytic Parallel Kinetic Resolution

Abstract: Chiral recognition leads to enantio‐ and regiodivergent reactivity: An unusual regiodivergent catalytic kinetic resolution has been accomplished for the first time in an organometallic reaction in which a C−C bond is formed. Chiral copper complexes of the non‐racemic phosphoramidite ligand L* discriminate the enantiomers of semirigid vinyloxiranes (having a blocked s‐cis or s‐trans conformation) to give separable regioisomeric products with very high stereocontrol in a two‐step process (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 27 publications
2
43
1
Order By: Relevance
“…Very interestingly, the complete conversion of a racemic allylic epoxide into constitutionally different enantiomerically enriched ring‐opened products,namely regioisomeric allylic and homoallylic alcohols of type 15 and 16 , was obtained simply by using an excess of the dialkylzinc reagent and a longer reaction time [Equation (b) in Scheme ] 69. This is one of the very rare examples of a regiodivergent kinetic resolution (RKR) by the use of a hard organometallic reagent and a chiral catalyst in a carbon–carbon bond‐forming reaction 70. More recently, we have shown that the RKR can be successfully applied to a variety of cyclic semi‐rigid allylic epoxides and, in some specific cases, also to conformationally mobile allylic epoxides 71…”
Section: Organometallic Reagentsmentioning
confidence: 99%
“…Very interestingly, the complete conversion of a racemic allylic epoxide into constitutionally different enantiomerically enriched ring‐opened products,namely regioisomeric allylic and homoallylic alcohols of type 15 and 16 , was obtained simply by using an excess of the dialkylzinc reagent and a longer reaction time [Equation (b) in Scheme ] 69. This is one of the very rare examples of a regiodivergent kinetic resolution (RKR) by the use of a hard organometallic reagent and a chiral catalyst in a carbon–carbon bond‐forming reaction 70. More recently, we have shown that the RKR can be successfully applied to a variety of cyclic semi‐rigid allylic epoxides and, in some specific cases, also to conformationally mobile allylic epoxides 71…”
Section: Organometallic Reagentsmentioning
confidence: 99%
“…6 Due to these requirements the reaction design of PKR is difficult; while several conceptual examples of PKR have been reported, very few practical implementations have emerged. [7][8][9] Enantiodivergence can also be achieved using a single chiral reagent or catalyst, most often leading to enantioenriched regioisomeric [10][11][12][13][14][15] or diastereomeric [16][17][18] products. Such processes are referred to as regiodivergent or stereodivergent reactions of racemic mixtures and they are more common in organic synthesis.…”
mentioning
confidence: 99%
“…Here, we report a diastereo-and enantioselective tandem conjugate addition-aldol cyclization of enone-diones, whereby two COC bonds and four contiguous stereogenic centers are created in a single manipulation with control of relative and absolute stereochemistry (Scheme 1). Through the use of chiral racemic enone-dione substrates, the first examples of parallel kinetic resolutions (24) by enantioselective conjugate addition are achieved (25)(26)(27)(28)(29)(30)(31)(32)(33). This new catalytic methodology enables concise entry to seco-B ring steroids possessing a cis-fused C-D ring junction with a bridgehead hydroxyl residue, as found in naturally occurring cardiotonic steroids derived from digitalis.…”
mentioning
confidence: 99%